Studies of the silkworm enzyme activity and their correlations with economic variables - Yeremenko, Sergiy; Wani, Mohd Younus; Ganie, Nisar Ahmad; Mir, Mushtaq Rasool; Mir, Shakeel Ahmad; Yaqoob, Munazah; Murtaza, Imtiyaz; Wani, Tanveer Ahmad; Baqual, Mohd Farooq; Sukennikov, Oleksii (Ecological Questions, 2023)
The experiment was conducted to analyse the larval performance and economic traits of bivoltine silkworm breeds of silkworm (SK-1, SK-6, SK-22, SK-28, SK-33, CSR4, CSR2, NB4D2, DUN6 and APS4) during spring season. The haemolymph total protein, succinate and gultamate dehydrogenase activities were estimated and their correlation with economic traits were also worked out. The results of the study confirmed that among ten bivoltine silkworm breeds, highest haemolymph SDH activity of 3.47 µmoles/ml/mgprotein/min was recorded in the silkworm breed SK1 and least SDH activity of 1.58 µmoles/ml/mg protein/min was recorded in the breed APS4. The highest peak of succinate dehydrogenase activity of 2.65 µmoles/ml/mg protein/min was observed on 7th day of the 5th instar and lowest peak of succinate dehydrogenase activity of 2.39 µmoles/ml/mg protein/min was observed on 4th day of the 5th instar. GDH activity of 0.46 µmoles/ml/mg protein/min was recorded highest in the silkworm breed SK1 and lowest of 0.15 µmoles/ml/mg protein/min was recorded in silkworm breed APS4. The highest peak of haemolymph GDH of 0.36 µmoles/ml/mg protein/min was recorded on 7th day of 5th instar and lowest peak of 0.26 µmoles/ml/mg protein/min was recorded on 4th day of 5th instar. The correlational studies revealed that haemolymph total protein, SDH and GDH were found to be positively corelated with yield by weight and number (cocoon), weight of mature larvae, shell weight ,cocoon weight, shell ratio percent, silk productivity, rate of pupation, fecundity, raw silk percentage and length of filament. Thus, the study revealed that silkworm breeds like SK1, SK6, SK22 and SK28 as productive breeds and hence may be used for future breeding programmes for evolution of new robust silkworm breeds